Identification of novel transcripts of CHRNA7 and CHRFAM7A in airway epithelial cells - Ahmad, Omar Akram Jerjees (2013)
Background: RNA splicing is a crucial process for delivering the appropriate message for protein synthesis. Most genes are affected by alternative splicing, and among these is CHRNA7. This gene encodes for the nicotinic acetylcholine α7 receptor subunit that is involved in the cholinergic anti-inflammatory pathway. This anti-inflammatory pathway is considered an important part of the human body’s defence line against tissue injury or infection and causative mechanism in COPD. Aim: The aim of the present study was to investigate the role of alternative splicing on the nature of the transcripts generated by CHRNA7 gene and its partial duplicate, CHRFAM7A. Methods: Airway epithelial cell lines, A549 and BEAS2B, were mainly used as targets for testing alternative splicing. RT-PCR, TA cloning and gel extraction methods were used for testing CHRNA7 and CHRFAM7A transcripts. Following RT-PCR, the resulting product band intensities were analysed using densitometric analysis tools. This was followed by the use of several bioinformatics analysis tools to predict the protein structure for the resulting transcripts. For one of the detected transcripts, minigene methods were used to test for the source of expression. Results: A novel transcript missing exon 9 is reported for the first time. Both genes showed the expression of full length and the novel transcripts (missing exon 9) at similar ratios (~2:1). These results could be detected in immortalised cell lines from human alveolar and bronchial epithelial cells (A549 and BEAS2B, respectively) and in BE (2)-c cells (neuroblastoma cells with bone marrow metastasis). The same results were shown when primary human peripheral blood monocytes cells (PBMC) were tested. This means that the effect of missing exon 9 is not tissue-specific, and is not only found in cancerous cells, indicating that it could be a common feature of splicing for these two genes. Furthermore, another novel transcript was detected which is inserted exon 9b. The initial RT-PCR experiments seemed to suggest that this was derived from CHRFAM7A only. The use of minigene methods showed that this transcript could be expressed from both genes, CHRNA7 and CHRFAM7A, but a single nucleotide base within the inserted sequence (at position 77 from the 5` end) could play a role in enhancing of exon 9b in the mRNA transcripts. This base is C allele in CHRFAM7A sequence of exon 9b, while its corresponding base in CHRNA7 is G allele that has less prominent effect on exon 9b inclusion. Conclusion: CHRNA7 and CHRFAM7A express novel transcripts in different human cells that are missing exon 9. This could be due to inactive splicing factors that are required for recognition of exon 9 as a constitutive exon. For exon 9b transcripts, these lie within the common sequence of CHRNA7 and CHRFAM7A, and it seems that the presence of C allele at position 77 could enhance the inclusion of exon 9b in CHRFAM7A more than the presence of G allele in CHRNA7 sequences. The results shown in this study implicate a possible regulatory role of the transcripts detected on the control mechanism exerted by CHRFAM7A on CHRNA7. These results help to suggest a possible role of in the development of COPD in the form of inflammatory/anti-inflammatory control imbalance.